PRESUPPOSITION AND COMMON GROUND IN GRETA THUNBERG’S SPEECH ON TACKLING CLIMATE CHANGE AT THE YOUTH4CLIMATE CONFERENCE 2021 - Hilwa Mubarak; Sari Rejeki; Agnes Setyowati (Journal Albion : Journal of English Literature, Language, and Culture, 2022)
The objectives of this study are to analyze the presuppositions and common ground in Greta Thunberg’s speech at the 2021 Youth4Climate conference. This study uses the descriptive-qualitative method. By using Yule’s theory, the utterances in Thunberg’s speech were analyzed into presupposition types. The classification of presuppositions helps to conclude the background belief, relating to an utterance that must be mutually known or assumed by the speaker and addressee. The results reveal that all types of presupposition exist in Thunberg’s utterances. The presuppositions are related to the tackling of climate change by world leaders. The common ground also illustrates a similar issue.Keywords: presupposition; presupposition types; common ground; climate change.